2017
DOI: 10.5830/cvja-2016-071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of proximal anastomosis on the expansion rate of a dilated ascending aorta in coronary artery bypass surgery: a prospective study

Abstract: SummaryBackground:This study was designed to determine the short- and long-term effects of proximal aortic anastomosis, performed during isolated coronary artery bypass grafting (CABG) in patients with dilatation of the ascending aorta who did not require surgical intervention.Methods:The study was performed on 192 (38 female and 160 male patients; mean age, 62.1 ± 9.2 years; range, 42–80 years) patients with dilatation of the ascending aorta who underwent CABG surgery between 1 June 2006 and 31 May 2014. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Balci et al in a study comparing pre-and postoperative echographic dimensions of the ascending aorta and the si-notubular junction in patients with CABG and a moderately dilated aorta found an increased expansion rate of these segments when a proximal anastomosis was constructed on the diseased aorta, proposing a disruption of the elastic structure and connective tissue of the aorta by the arteriotomy as a possible mechanism [12]. In contrast, we found that the moderately dilated aorta, unreplaced during car- Fate of the moderately diseased aorta: a single-center experience diac surgery, did not dilate further during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Balci et al in a study comparing pre-and postoperative echographic dimensions of the ascending aorta and the si-notubular junction in patients with CABG and a moderately dilated aorta found an increased expansion rate of these segments when a proximal anastomosis was constructed on the diseased aorta, proposing a disruption of the elastic structure and connective tissue of the aorta by the arteriotomy as a possible mechanism [12]. In contrast, we found that the moderately dilated aorta, unreplaced during car- Fate of the moderately diseased aorta: a single-center experience diac surgery, did not dilate further during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%